Assessment of Elderlies Sleep Disorders and Different Confronts Methods Among Them - Monir Nobahar; Abas Ali Vafai (Sālmand, 2007)
Objectives: Sleep is one of the essential needs for human and every disorder in during of sleep causes psychological problem and decreased person>s ability. Although sleep disorders occur in every of ages. Elderly person usually has very problem for satisfied sleep. The aim of this study was to estimate prevalence of sleep disorders and confront methods of those in elderly persons in Semnan city.